2017
DOI: 10.1186/s13054-017-1890-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of three topical antiseptic solutions for the prevention of catheter colonization: a multicenter randomized controlled study

Abstract: BackgroundTo compare the efficacy of three antiseptic solutions [0.5%, and 1.0% alcohol/chlorhexidine gluconate (CHG), and 10% aqueous povidone-iodine (PVI)] for the prevention of intravascular catheter colonization, we conducted a randomized controlled trial in patients from 16 intensive care units in Japan.MethodsAdult patients undergoing central venous or arterial catheter insertions were randomized to have one of three antiseptic solutions applied during catheter insertion and dressing changes. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Whether these methods are applicable to the situation of indwelling abdominal drains should be further explored by future studies. Yasuda et al compared the efficacy of different antiseptic solutions in preventing intravascular catheter colonization (29). 0.5% and 1.0% alcohol/ chlorhexidine gluconate were found to be superior than 10% povidone iodine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether these methods are applicable to the situation of indwelling abdominal drains should be further explored by future studies. Yasuda et al compared the efficacy of different antiseptic solutions in preventing intravascular catheter colonization (29). 0.5% and 1.0% alcohol/ chlorhexidine gluconate were found to be superior than 10% povidone iodine.…”
Section: Discussionmentioning
confidence: 99%
“…Although the technical safety and clinical efficacy of indwelling abdominal drains for advanced cancer patients with refractory ascites have been demonstrated (3)(4)(5)(6)(7)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), bacterial colonization and subsequent drain-related infection remain to be common concerns for these types of long-term drains inserted into the peritoneal cavity as in patients with other types of long-term indwelling catheters, for example, Tenckhoff catheters (26), central venous access (27)(28)(29) and urinary catheters (30). Colonization of these catheters can lead to resistance to antibiotic treatment because of the formation of bacterial biofilm (31)(32)(33).…”
Section: Bacterial Colonization and Drain-related Infectionmentioning
confidence: 99%
“…Skin decontamination prior to PIVC insertion has rarely been the topic of high quality randomized controlled trials. Instead, clinical practice is based on extrapolation from central venous catheter studies, where CHG has been demonstrated to be superior to other decontaminants in preventing infections (Lai et al, 2016;Mimoz et al, 2015;Yasuda et al, 2017). However, the current study demonstrates the lack of evidence specific to PIVCs, and practice appears to vary based on product availability rather than clinical indication.…”
Section: Discussionmentioning
confidence: 80%
“…74 A third RCT compared two chlorhexidine concentrations (0.5% or 1.0% in 79% ethanol) with povidone-iodine (10% without alcohol), reporting equivocal evidence for colonization (Category A3-E evidence) and catheter-related bloodstream infection (Category A3-E evidence). 75 A quasiexperimental study (secondary analysis of an RCT) reports a lower rate of catheter-related bloodstream infection with chlorhexidine (2% with 70% alcohol) than povidone-iodine (5% with 69% alcohol) (Category B1-B evidence). 76 The literature is insufficient to evaluate the safety of antiseptic solutions containing chlorhexidine in neonates, infants and children.…”
Section: Selection Of Antiseptic Solutionmentioning
confidence: 99%